INCREASED EXPRESSION OF HER2, HER3 and HER2:HER3 HETERODIMERS IN HPV-POSITIVE HNSCC USING A NOVEL PROXIMITY-BASED ASSAY: IMPLICATIONS FOR TARGETED THERAPIES - Pollock, Netanya I. (Clin Cancer Res, 2015)
PURPOSE: In other cancer types, HPV infection has been reported to coincide with overexpression of HER2 and HER3, however the association between HER2 or HER3 expression or dimer formation in HNSCC has not been reported. Overexpression of HER2 and HER3 may contribute to resistance to EGFR inhibitors, including cetuximab, although the contribution of HPV in modulating cetuximab response remains unknown. Determination of heterodimerization of HER receptors is challenging and has not been reported in HNSCC. The present study aimed to determine the expression of HER proteins in HPV[+] versus HPV[−] HNSCC tumors using a proximity-based protein expression assay (VeraTag), and to determine the efficacy of HER targeting agents in HPV[+] and HPV[−] HNSCC cell lines. EXPERIMENTAL DESIGN: Expression of total HER1, HER2, and HER3, p95HER2, p-HER3, HER1:HER1 homodimers, HER2:HER3 heterodimers and the HER3-PI3K complex in 88 HNSCC was determined using VeraTag, including 33 baseline tumors from individuals treated in a trial including cetuximab. Inhibition of cell growth and protein activation with cetuximab and afatinib was compared in HPV[+] and HPV[−] cetuximab-resistant cell lines. RESULTS: Expression of total HER2, total HER3, HER2:HER3 heterodimers, and the HER3:PI3K complex were significantly elevated in HPV[+] HNSCC. Total EGFR was significantly increased in HPV[−] HNSCC where VeraTag assay results correlated with IHC. Afatinib significantly inhibited cell growth when compared to cetuximab in the HPV[+] and HPV[−] cetuximab-resistant HNSCC cell lines. CONCLUSION: These findings suggest that agents targeting multiple HER proteins may be effective in the setting of HPV[+] HNSCC and/or cetuximab resistance.